Investigating the English needs of law department students in English for specific purposes - Rumalessin, Ummu Artha Tsary; Farah, Rafika Rabba (Universitas Muhammadiyah Sidoarjo, 2021)
This present study aims at investigating the students’ target needs in learning ESP Speaking of Law department students. The adapted version of Aliakbari & Boghayeri’s (2014) and Alsamadani’s (2017) questionnaire was used as the main instrument of this study to understand the 45 students’ perception about their needs in learning ESP speaking course. A mixed-method research design was implemented in this present research. Students’ responses were analyzed statistically using SPSS 16.0 by calculating the mean, frequency and percentage. To elicit more understanding on the topic, interview was implemented to senior students in order to get deeper investigation about students’ target needs. The interview data were then analyzed using NVivo 12 Plus. This study reveals that most of the students’ needs are concerned with their professional job in the future so they are able to use English in their fields. Thus, this study provides some highlighting points on what to include in course development. In such a notion, this study suggests lecturers provide specific materials related to law in order to face their professional life either in short- or long-term future needs. . HIGHLIGHTS: This study pinpoints the result of Law students measurement on their self-rating towards their English competences. This study highlights on materials related to Law department that are perceived to be strongly needed and less needed. This study also reveals that according to students’ interview transcript, their needs in learning ESP are found to attain long-term goal compared to the short-term one.